Trade liberalisation and climate change: A CGE analysis of the impacts on global agriculture - Alvaro Calzadilla; Katrin Rehdanz; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
Based on predicted changes in the magnitude and distribution of global precipitation, temperature and river flow under the IPCC SRES A1B and A2 scenarios, this study assesses the potential impacts of climate change and CO2 fertilization on global agriculture, and its interactions with trade liberalisation as proposed for the Doha Development Round. The analysis uses the new version of the GTAP-W model, which distinguishes between rainfed and irrigated agriculture and implements water as an explicit factor of production for irrigated agriculture. Significant reductions in agricultural tariffs lead to modest changes in regional water use. Patterns are non-linear. On the regional level water use may go up for partial liberalization, and down for more complete liberalization. This is because different crops respond differently to tariff reductions, and because trade and competition matter too. Moreover, trade liberalization tends to reduce water use in water scarce regions, and increase water use in water abundant regions, even though water markets do not exist in most countries. Considering impacts of climate change the results show that global food production, welfare and GDP fall over time while food prices increase. Larger changes are observed under the SRES A2 scenario for the medium term (2020) and under the SRES A1B scenario for the long term (2050). Combining scenarios of future climate change with trade liberalization countries are affected differently. However, the overall effect on welfare does not change much.
Keywords: 330; climate change; computable general equilibrium; trade liberalization; water policy; water scarcity